THE SYSTEMATIC STUDY OF MAGNETIC PROPERTIES OF TOP LAYER SOME SOILS IN LEFT BANK UKRAINE - SUKHORADA, A.; KRUHLOV, O.; MENSHOV, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The study the magnetic susceptibility of soil’s top laier in Left-blank Ukraine. The main features of disribution of magnetic properties in typical soils from Ukraine in the class of eastern-european landscapes are considered.